SISTEM INFORMASI ARUS KAS BERBASIS MULTI USER PADA SEKOLAH KB-TK KRISTEN DIAN WACANA DEMAK - Kasih Purwantini; Elisa Satyaningrum; Arsito Ari Kuncoro (Universitas Sains dan Teknologi Komputer, 2020)
Dian Wacana Demak Christian Kindergarten-Kindergarten School, which is one of the agencies engaged in the science and early childhood education. The type of data used is qualitative and quantitative data. The research objective is to design an effective and efficient school financial administration recording information system and design a school financial administration recording information system that has a system security that can maintain the correctness of the data. The research method used is the Borg and Gall R&D Development Research model, the Prototyping System Development Method to produce a product in the form of a prototype with 6 stages: Research and Data Collection, Planning, Initial Product Development, Product Testing, Product Revision, Final Trial. The conclusion from the results of this study is that this system can facilitate the recording of cash in and cash out transactions so that there are no mistakes in recording, users can easily present cash reports more quickly so that they can minimize recording time and recording errors, and make it easier for users to print. cash reports with accurate results so as to support and speed up decision making.